Understanding the dynamics of deceased organ donation and utilization in Colombia - William Cruz Mususú; Andrea García-Lopez; Nicolás Lozano-Suarez; Andrea Gómez-Montero; Milena Orellano-Salas; Luisa Vargas-Pérez; Ximena Escobar-Chaves; Fernando Girón-Luque (Revista Panamericana de Salud Pública, 2024)
Objective. To obtain a comprehensive overview of organ donation, organ utilization, and discard in the entire donation process in Colombia. Methods. A retrospective study of 1 451 possible donors, distributed in three regions of Colombia, evaluated in 2022. The general characteristics, diagnosis, and causes of contraindication for potential donors were described. Results. Among the 1 451 possible donors, 441 (30.4%) fulfilled brain death criteria, constituting the potential donor pool. Families consented to organ donation in 141 medically suitable cases, while 60 instances utilized legal presumption, leading to 201 eligible donors (13.9%). Of those, 160 (11.0%) were actual donors (in whom operative incision was made with the intent of organ recovery or who had at least one organ recovered). Finally, we identified 147 utilized donors (10.1%) (from whom at least one organ was transplanted). Statistically significant differences were found between age, sex, diagnosis of brain death, and donor critical pathway between regions. A total of 411 organs were transplanted from 147 utilized donors, with kidneys being the most frequently procured and transplanted organs, accounting for 280 (68.1%) of the total. This was followed by 85 livers (20.7%), 31 hearts (7.5%), 14 lungs (3.4%), and 1 pancreas (0.2%). The discard rate of procured deceased donors was 8.1%. Conclusions. About one-tenth of donors are effectively used for transplantation purposes. Our findings highlight areas of success and challenges, providing a basis for future improvements in Colombia.